Nilai-nilai Religius dalam Syair Selawat Dulang di Kelurahan Koto Pulai Kecamatan Koto Tangah Kota Padang - Santi, Purma Dwi; Amir, Amril; Hamidin, Hamidin (Universitas Negeri Padang, 2013)
This research is aimed to describe religious values in Salawat Dulang lyric including aqidah value, syariah, and akhlak in Kelurahan Koto Pulai Kecamatan Koto Tangah Padang.This research is qualitative research using descriptive method that emphasizes on content analyzing. This research uses writing the script technique or something that is written by selawat dulang player in the interview as the collecting data technique by using analyze data instrument. Every script is written on the interview and it is read again of the lyric, translate it into indonesian language and invent religious values: aqidah, syariah and akhlak. Then, analyze the data based on the classification that is found, make a summary, and report the research result.